Penggunaan Obat Hisap Bagi Penderita Asma Pada Waktu Berpuasa Dalam Kajian Filsafat Hukum Islam - ilham, ilham al-basowi al basowi; Busyro, Busyro Busyro (Tasamuh: Jurnal Studi Islam, 2023)
People with asthma really need inhalers to support their health. Contemporary fiqh experts differ in two opinions regarding the law of using this inhaler while fasting, whether it breaks the fast so it is mandatory to replace the fast or not. This research is classified as library research, data was collected by quoting and analyzing sources from books or literature that can support the discussion. This. The aim of this research is to find out the Islamic legal philosophy of using inhalants for asthma sufferers when fasting. So the philosophy of Islamic law regarding the use of inhalation drugs. Ulama who are of the opinion that using inhalation drugs breaks the fast, there are those who do not break the fast, scholars who are of the opinion that breaking the fast and not breaking the fast make ijtihad using the maqasid daruriyah method, they differ in their view of whether the inhalation enters the throat, or not